Systematic review of behavioural smoking cessation interventions for older smokers from deprived backgrounds - Graham Moore; Mala Mann; Annmarie Nelson; Kate Brain; Pamela Smith; Ria Poole (BMJ Open)
Introduction The associations between smoking prevalence, socioeconomic group and lung cancer outcomes are well established. There is currently limited evidence for how inequalities could be addressed through specific smoking cessation interventions (SCIs) for a lung cancer screening eligible population. This systematic review aims to identify the behavioural elements of SCIs used in older adults from low socioeconomic groups, and to examine their impact on smoking abstinence and psychosocial variables.Method Systematic searches of Medline, EMBASE, PsychInfo and CINAHL up to November 2018 were conducted. Included studies examined the characteristics of SCIs and their impact on relevant outcomes including smoking abstinence, quit motivation, nicotine dependence, perceived social influence and quit determination. Included studies were restricted to socioeconomically deprived older adults who are at (or approaching) eligibility for lung cancer screening. Narrative data synthesis was conducted.Results Eleven studies met the inclusion criteria. Methodological quality was variable, with most studies using self-reported smoking cessation and varying length of follow-up. There were limited data to identify the optimal form of behavioural SCI for the target population. Intense multimodal behavioural counselling that uses incentives and peer facilitators, delivered in a community setting and tailored to individual needs indicated a positive impact on smoking outcomes.Conclusion Tailored, multimodal behavioural interventions embedded in local communities could potentially support cessation among older, deprived smokers. Further high-quality research is needed to understand the effectiveness of SCIs in the context of lung screening for the target population.PROSPERO registration number CRD42018088956.